3D Biomimetic Cultures: The Next Platform for Cell Biology. Issue 11 (November 2016) - Chen, Christopher S.
Abstract : Advances in engineering of cells and culture formats have led to the development of a new generation of 3D cultures that can recapitulate a variety of multicell-type, morphogenetic behaviors that were previously largely observable only in in vivo settings. Ultimately, these systems are likely to be assimilated into and forever change the landscape of biomedical research.